Evaluasi Simpang Tidak Bersinyal Dengan Penggunaan Software Vissim : Studi Kasus Simpang Tiga Monumen Emmy Saelan - Indryady.S, Muhammad Wahyu; Yunianti, Nurhadijah; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Traffic movements at intersections are generally regulated by traffic control. This is intended to create safety as well as smooth traffic flow at the intersection. At the Emmy Saelan Monument Intersection in Makassar City, there is no proper traffic regulation. Therefore, it is often found that there are long queues and vehicle delays that occur at the intersection due to high traffic flow. Based on these problems, it is necessary to conduct research with the aim of improving the performance of the intersection with indicators in the form of queue values and delay times at the intersection. The method used in this research is to use direct observation methods and manual calculations and perform simulations using Vissim Software. Several alternative intersection treatments are given to overcome existing intersection problems, namely by implementing 2-phase and 3-phase traffic signals, The recommended alternative handling is in the form of implementing a 2-phase signalized traffic signal because it can reduce queues and delays significantly compared to existing conditions.